Digital Interfaith Citizenship: Analisis Narasi 'Mikro Kerukunan' Generasi Z di Platform Tiktok - Cindy Nova Riyanti; Muhamad Tamamul Iman (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study explores how Generation Z in Indonesia produces and spreads narratives of micro-interfaith harmony through the TikTok platform. Amid growing social polarization in digital spaces, casual and personal tolerance content created by Gen Z offers a new approach to building social cohesion. Using a qualitative netnography method, this research observes 20 viral videos with over 10,000 views during the 2024-2025 Ramadan period, including the War Takjil trend and the #LoginLintasIman campaign, as forms of affective digital citizenship. The findings reveal that TikTok’s algorithmic logic, driven by emotional engagement, allows grassroots narratives of tolerance to reach broad audiences organically. Within this ecosystem, values of pluralism and solidarity are not shaped by formal institutions but emerge from the participatory dynamics and digital habitus of Gen Z. This study concludes that a new form of digital interfaith citizenship is emerging, termed algorithmic harmony, where tolerance is fostered through affective interactions, viral distribution, and the everyday media practices of youth. The findings provide new insights for media studies, diversity education, and digital tolerance discourse.